Trigger Finger Hand, Pathophisiology and Management - Elviena Shaffiranisa; Dinda Puspita Sari; Andhito Rafid Chusaeri; Baiq Ayu Rahmawati; Zhayyin Palna Rial Novsyaini; Tomi Irmayanto (Jurnal Biologi Tropis, 2023)
Trigger finger hand is a stenosing tenosynovitis that occurs in the flexor sheaths of the finger and thumb due to repetitive use. Narrowing of the flexor sheath combined with hypertrophy and inflammation between tendons and sheaths causes trigger finger stenosing tenosynovitis leading to tendon restriction. The purpose of this literature review to provide an update regarding the pathophysiology and management of trigger finger. This literature study using search engines including Pubmed, ScienceDirect, NCBI, and Google Schoolar. In total, 10 sources were used which were obtained from various existing databases. In the treatment of trigger finger, there are non-surgical treatments such as conservative management and conventional management, and surgical management, namely Open release pulley A-1 which is the first line of treatment before medical rehabilitation, medical rehabilitation.